Evaluation of passive polarized stereoscopic 3D display for visual & mental fatigues - Amin, H.U. (Institute of Electrical and Electronics Engineers Inc., 2015)
Visual and mental fatigues induced by active shutter stereoscopic 3D (S3D) display have been reported using event-related brain potentials (ERP). An important question, that is whether such effects (visual & mental fatigues) can be found in passive polarized S3D display, is answered here. Sixty-eight healthy participants are divided into 2D and S3D groups and subjected to an oddball paradigm after being exposed to S3D videos with passive polarized display or 2D display. The age and fluid intelligence ability of the participants are controlled between the groups. ERP results do not show any significant differences between S3D and 2D groups to find the aftereffects of S3D in terms of visual and mental fatigues. Hence, we conclude that passive polarized S3D display technology may not induce visual and/or mental fatigue which may increase the cognitive load and suppress the ERP components. Â© 2015 IEEE.